Vulnerabilidades sociais e rupturas na transição para a vida adulta - Paula Guerra (2004)
The diversity of situations in which one can find the youth at present takes some consistency to this type of approach, which tends to regard them as a standardizing, without which indeed they are. The young appear above, in some studies, as a vulnerable category to the phenomena of poverty and social exclusion. When speaking to young people vulnerable to exclusion as a category, you must take into account some aspects that contribute to this phenomenon, such as the problems related to education, employment, among others.